2015
DOI: 10.1128/aem.03588-14
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Methane-Cycling Archaea in Hydrothermal Sediment Investigated by General and Group-Specific PCR Primers

Abstract: bThe zonation of anaerobic methane-cycling Archaea in hydrothermal sediment of Guaymas Basin was studied by general primer pairs (mcrI, ME1/ME2, mcrIRD) targeting the alpha subunit of methyl coenzyme M reductase gene (mcrA) and by new groupspecific mcrA and 16S rRNA gene primer pairs. The mcrIRD primer pair outperformed the other general mcrA primer pairs in detection sensitivity and phylogenetic coverage. Methanotrophic ANME-1 Archaea were the only group detected with groupspecific primers only. The detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 82 publications
3
61
1
1
Order By: Relevance
“…Therefore, the Guaymas Basin represents a unique opportunity to directly compare hydrothermal vent and cold seep ecosystems. Previous investigations on the sedimentary microbial community compositions of the Guaymas Basin, from either but not both of these ecosystems, suggested that analogous microbial processes might occur, despite contrasted temperatures (Teske et al, 2002;Dhillon et al, 2003;McKay et al, 2012;Vigneron et al, 2013;Cruaud et al, 2015;Lever and Teske, 2015). However, these results remain hardly comparable since different methodologies were used.…”
contrasting
confidence: 43%
“…Therefore, the Guaymas Basin represents a unique opportunity to directly compare hydrothermal vent and cold seep ecosystems. Previous investigations on the sedimentary microbial community compositions of the Guaymas Basin, from either but not both of these ecosystems, suggested that analogous microbial processes might occur, despite contrasted temperatures (Teske et al, 2002;Dhillon et al, 2003;McKay et al, 2012;Vigneron et al, 2013;Cruaud et al, 2015;Lever and Teske, 2015). However, these results remain hardly comparable since different methodologies were used.…”
contrasting
confidence: 43%
“…GB is the first hydrothermal vent habitat where the MAO process was detected (Teske et al, 2002). Diverse methane-oxidizing archaea belonging to ANME-1 and ANME-2 have been frequently detected by 16S rRNA and mcrA gene surveys at GB (Holler et al, 2011;Biddle et al, 2012;Vigneron et al, 2013;Lever and Teske, 2015;Dowell et al, 2016;McKay et al, 2016). Although, the archaeal multi-carbon alkane oxidizer Ca.…”
Section: Abundance and Activity Of Diverse Mao Processes In Gbmentioning
confidence: 99%
“…However, our current knowledge on the whole archaeal biology and ecology potentials is yet strongly biased by the difficulties in culturing, the still limited use of powerful metagenomic approaches (Rinke et al ., ; Castelle et al ., ) and the very few properly compiling studies homogeneously focused on a key functional archaeal gene of major ecological interest (e.g. the amoA gene, Pester et al ., , Fernàndez‐Guerra and Casamayor, ; or the mcrA gene Lever and Teske ). Large environmental surveys may also add clues on the ecology and biology of the uncultured archaea and unveil ecological patterns and environmental preferences.…”
Section: Introductionmentioning
confidence: 99%